PROBLEMS ARISING IN THE CONSTRUCTION OF A NEW-GENERATION SEISMIC INTENSITY SCALE - Aptikaev F.F. (My University, 2000)
Results of macroseismic and instrumental investigations were summarized to formulate the basic requirements on an intensity scale. Several empirical relations are quoted to show that these requirements are indispensable. The existing scales are examined for their merits and drawbacks. Ways to enhance the accuracy of an intensity scale are discussed.